Airway mir-155 responses are associated with TH1 cytokine polarization in young children with viral respiratory infections. - Maria Arroyo; Kyle Salka; Elizabeth Chorvinsky; Xilei Xuchen; Karima Abutaleb; Geovanny F Perez; Jered Weinstock; Susana Gaviria; Maria J Gutierrez; Gustavo Nino (PLoS ONE, 2020)
Background MicroRNAs (miRs) control gene expression and the development of the immune system and antiviral responses. MiR-155 is an evolutionarily-conserved molecule consistently induced during viral infections in different cell systems. Notably, there is still an unresolved paradox for the role of miR-155 during viral respiratory infections. Despite being essential for host antiviral TH1 immunity, miR-155 may also contribute to respiratory disease by enhancing allergic TH2 responses and NFkB-mediated inflammation. The central goal of this study was to define how airway miR-155 production is related to TH1, TH2, and pro-inflammatory cytokine responses during naturally occurring viral respiratory infections in young children. Methods Normalized nasal airway levels of miR-155 and nasal protein levels of IFN-γ, TNF-α, IL-1β, IL-13, IL-4 were quantified in young children (≤2 years) hospitalized with viral respiratory infections and uninfected controls. These data were linked to individual characteristics and respiratory disease parameters. Results A total of 151 subjects were included. Increased miR-155 levels were observed in nasal samples from patients with rhinovirus, RSV and all respiratory viruses analyzed. High miR-155 levels were strongly associated with high IFN-γ production, increased airway TH1 cytokine polarization (IFN-γ/IL-4 ratios) and increased pro-inflammatory responses. High airway miR-155 levels were linked to decreased respiratory disease severity in individuals with high airway TH1 antiviral responses. Conclusions The airway secretion of miR-155 during viral respiratory infections in young children is associated with enhanced antiviral immunity (TH1 polarization). Further studies are needed to define additional physiological roles of miR-155 in the respiratory tract of human infants and young children during health and disease.